Analisis Pengakuan Pendapatan dan Beban Pada PTPN III (Persero) Medan - Purba, Carolina Frakusya; Sihombing, Halomoan; Siboro, Danri T (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to determine whether the recognition of revenues and expenses at PT Perkebunan Nusantara III (Persero) Medan is by financial accounting standards. This study's primary and secondary data sources are primary and secondary. Data collection techniques in this study were interviews and documentation. The data analysis methods used in this research are descriptive and comparative analysis. At PT Perkebunan Nusantara III (Persero) Medan, the method applied in revenue recognition is the accrual basis. Revenue is recognized based on the amount of money received from customers less expenses. At PT Perkebunan Nusantara III (Persero), Medan expenses are recognized in the financial statements by the basis used, namely the accrual basis; the expenses are recognized when the transaction occurs. The results show that the company has applied the revenue recognition method according to PSAK.72, where revenue is recognized when the asset is transferred to the customer.